Developing mental health services in the global south - Fernando, Suman (Informa UK Limited, 2019)
This paper outlines the diversity of medical and healing systems indigenous to many regions of the world and their under-development and suppression during colonialism; describes briefly social and cultural changes that have taken place in the Global South after de-colonisation, resulting in varying degrees of a plurality (in terms of cultural style) of mental health systems currently available; summarizes important general principles of post-colonial development in the Global South; and, finally, points to ways of mental health and wellbeing development in the Global South by drawing on the example of Sri Lanka where the author was involved in a four-year research and capacity building project between 2007 and 2012. The paper takes a historical post-colonial approach to development on the principals of sustainability and cultural relevance and argues for a pragmatic approach in the short term while building up a body of knowledge about the countries concerned, their ground realities and their indigenous psychologies.